An oxidative cyclization reaction based fluorescent "Turn-On" probe for highly selective and rapid detection of hypochlorous acid. Issue 12 (21st March 2018) - Chen, Bo; Fu, Hongyu; Lv, Yaohong; Li, Xin; Han, Yifeng
Graphical abstract: Highlights: A novel hypochlorous acid-initiated oxidative intramolecular cyclization based fluorescent probe has been developed. The probe features rapid detection kinetics (<15 s). The probe shows high degree of selectivity and sensitivity for HClO. Abstract: A novel fluorescent turn-on probe, PHC1, for the detection of hypochlorous acid has been developed based on hypochlorous acid-initiated oxidative intramolecular cyclization. Endowed by the fast reaction rate, PHC1 features rapid detection kinetics, as well as high degree of selectivity and sensitivity for HClO.